Keywords for children's literature - Nel, Philip 1969-; Paul, Lissa 1953-; Christensen, Nina 1968- (Keywords, 2021)
An updated vocabulary for children's literature and cultureOver the past decade, there has been a proliferation of exciting new work across many areas of children's literature and culture. Mapping this vibrant scholarship, the Second Edition of Keywords for Children's Literature presents original essays on essential terms and concepts in the field. Covering ideas from "Aesthetics" to "Voice," an impressive multidisciplinary cast of scholars explores and expands on the vocabulary central to the study of children's literature.The second edition of this Keywords volume goes beyond disciplinary and national boundaries. Across fifty-nine print essays and nineteen online essays, it includes contributors from twelve countries and an international advisory board from over a dozen more. The fully revised and updated selection of critical writing-more than half of the essays are new to this edition-reflects an intentionally multinational perspective, taking into account non-English traditions and what childhood looks like in an age of globalization. All authors trace their keyword's uses and meanings: from translation to poetry, taboo to diversity, and trauma to nostalgia, the book's scope, clarity, and interdisciplinary play between concepts make this new edition of Keywords for Children's Literature essential reading for scholars and students alike